2017
DOI: 10.1080/1828051x.2017.1291282
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weaning age and milk feeding volume on growth performance of Nili-Ravi buffalo calves

Abstract: The objective of this study was to evaluate the growth performance of early or late weaned Nili-Ravi buffalo calves offered feeding regimes of low or high milk volumes. For this purpose, 48-day-old buffalo calves were randomly allocated to four treatments of twelve calves each. Calves were weaned either at day 56 (early weaned) or 84 (late weaned). Within each weaning age calves were offered milk at either 10% (low milk) or 15% (high milk) of their body weight. Early weaned calves were offered milk adjusted we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
2
6
1
Order By: Relevance
“…Comparing the performance ADG of buffalo between 0-3 months up to 24 to 30 months, it is revealed that weight gains and growth rates were higher during the periods when the calves were offered milk than when offered solid feed. In addition, the higher ADG before weaning age could be due to underdevelopment of the rumen buffalo calves at an early age, as observed and reported by Abbas et al [30].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Comparing the performance ADG of buffalo between 0-3 months up to 24 to 30 months, it is revealed that weight gains and growth rates were higher during the periods when the calves were offered milk than when offered solid feed. In addition, the higher ADG before weaning age could be due to underdevelopment of the rumen buffalo calves at an early age, as observed and reported by Abbas et al [30].…”
Section: Discussionsupporting
confidence: 66%
“…Following birth, both Swamp and Murrah crossbred buffaloes showed rapid pre-weaning growth, but the crossbred buffaloes showed significantly better rate, leading to a better overall daily weight gain of 0.86 kg/day compared to 0.65 and 0.74 kg/day at three months old reported by [ 29 , 30 ]. As a result, the average body weight of three-month-old buffaloes in the present study (112.29 kg) was higher than the 86.5 kg reported earlier [ 29 ].…”
Section: Discussionmentioning
confidence: 92%
“…In pre-weaned ruminants, the intake of solid feed is affected by milk management (e.g., amount of milk, age at weaning, and weaning method) and both access to and the type of solid feed offered ( Khan et al, 2011 ; Abbas et al, 2017 ). The above was observed in the present study in P01, where pre-weaning milk management and type of solid diet access resulted in differences in solid DMI.…”
Section: Discussionmentioning
confidence: 99%
“…Early weaning of buffalo calves cost approximately 18% less per kg of live weight than late weaning, which is associated with lower milk consumption (Abbas et al 2017, Bharti et al 2018. Yadav et al (1999) reported that growth rate of female buffalo calves weaned at 6-7 months in individual stall-fed was more than the calves which were grazed and group fed.…”
Section: Effect Of Weaning On Growth Of Calvesmentioning
confidence: 99%